2011
DOI: 10.1016/j.mcn.2011.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Differential subcellular distribution of rat brain dopamine receptors and subtype-specific redistribution induced by cocaine

Abstract: We investigated the subcellular distribution of dopamine D 1 , D 2 and D 5 receptor subtypes in rat frontal cortex, and examined whether psychostimulant-induced elevation of synaptic dopamine could alter the receptor distribution. Differential detergent solubilization and density gradient centrifugation were used to separate various subcellular fractions, followed by semi-quantitative determination of the relative abundance of specific receptor proteins in each fraction. D 1 receptors were predominantly locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 65 publications
2
42
0
Order By: Relevance
“…For instance, repeated cocaine administration (20 mg/kg, i.p.) for seven days induces translocation of dopamine receptors in rat frontal cortex [37]. Moreover, dopamine D1 receptors (D1R) translocate from lipid raft to non-lipid raft and the cytoplasmic fractions of the frontal cortex following cocaine treatment whereas the localization of dopamine D5 receptors (D5R) and dopamine D2 receptors (D2R) were not significantly altered.…”
Section: Psychostimulants Lipid Rafts and Dopamine Transporters/recementioning
confidence: 97%
“…For instance, repeated cocaine administration (20 mg/kg, i.p.) for seven days induces translocation of dopamine receptors in rat frontal cortex [37]. Moreover, dopamine D1 receptors (D1R) translocate from lipid raft to non-lipid raft and the cytoplasmic fractions of the frontal cortex following cocaine treatment whereas the localization of dopamine D5 receptors (D5R) and dopamine D2 receptors (D2R) were not significantly altered.…”
Section: Psychostimulants Lipid Rafts and Dopamine Transporters/recementioning
confidence: 97%
“…Dopamine D 1 Rs were found to interact with caveolin-1 in both COS-7 and in the rat brain (Kong et al, 2007;Voulalas et al, 2011). In COS-7 cells, upon D 1 R agonist binding, there is an increased partition of the receptor to lipid rafts and internalization through caveolae (Kong et al, 2007).…”
Section: Dopaminergic Transmissionmentioning
confidence: 99%
“…In COS-7 cells, upon D 1 R agonist binding, there is an increased partition of the receptor to lipid rafts and internalization through caveolae (Kong et al, 2007). Interestingly, cocaine administration for several days, which presumably leads to sustained changes in the degree of activation of dopaminergic receptors, causes a shift of D 1 R to non-raft fractions in the rat frontal cortex (Voulalas et al, 2011). In clear contrast with the D 1 R, which within the rat frontal cortex is mostly localized to lipid rafts, the dopamine D 2 R or D 5 R are predominantly outside the rafts, in spite of their different distribution among cytoplasmic, detergent-soluble and detergentresistant membrane fractions (Voulalas et al, 2011).…”
Section: Dopaminergic Transmissionmentioning
confidence: 99%
“…It has been suggested that serotonin depletion could be mediated by serotonindopamine interactions, in which a deficient inhibitory effect of serotonin on dopaminergic neurons would result in a higher dopamine activity (Harrison et al, 1997). It may be noted that D 1 R dopamine receptors, in contrast to D 2 R, are localized in lipid rafts and interact with Caveolin-1 (at least in the rat frontal cortex) (Voulalas et al, 2011), and that cholesterol changes could affect dopaminergic activity. Interestingly, cocaine leads to the migration of D 1 R from lipid to non-raft fractions in rats (Voulalas et al, 2011), possibly explaining why cocaine use is associated with suicidal behavior (Vijayakumar et al, 2011).…”
Section: Cholesterol and Suicidal Behavior: Neurochemical Connectionsmentioning
confidence: 99%